Psychological skills of Malang State University athletes who participate in POMPROV 2022 - Moch. Ghossam Azim; Kurniati Rahayuni; Prisca Widiawati (Indonesian Journal of Research in Physical Education, Sport, and Health, 2023)
Achievement sports are a form of activity that requires a psychological aspect. The psychological aspect of athletes at the State University of Malang is the key to victory in winning the overall champion of POMPROV 2022. ACSI-28 (Athletic coping stress Inventory-28) is a psychological benchmark in sports achievement, namely (1) coping with advertising; (2) peaking under pressure; (3) goal setting/mental preparation (4) concentration; (5) free from worry; (6) confidence and achievement motivation;" and (7) coachability. This research was conducted to find out the psychological skills of State University of Malang athletes who took part in POMPROV 2022 using ACSI-28. Athletes who filled out the ACSI-28 questionnaire were 45 people through google forms. Analysis of ACSI-28 calculation data or psychological aspects of State University of Malang athletes who took part in POMPROV 2022 is still in the medium and high categories. This research was conducted to find out how big the psychological aspects of State University of Malang athletes who participated in POMPROV 2022 and as a study of coaches in measuring the psychology needed by athletes.